2-(3-Nitrophenoxy)Quinoxaline - Hassan, N.D.; Abdullah, Z.; Tajuddin, Hairul Anuar; Fairuz, Z.A.; Ng, S.W.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
In the title molecule, C(14)H(9)N(3)O(3), the dihedral angle between the quinoxaline and benzene rings is 77.13 (9)degrees. The molecule is twisted about the ether-benzene O-C bond, with a C-O-C-C torsion angle of -102.8 (2)degrees. In the crystal, molecules are linked by C-H center dot center dot center dot O hydrogen bonds, forming layers in the ab plane, with one nitro O atom accepting two such interactions. The layers stack along the c-axis direction via weak C-H center dot center dot center dot pi interactions.